Superoleophilic-hydrophobic Kapok oil sorbents via energy efficient carbonization - Yunos, Normaisarah; Müller, Julian; Chen, Soo Kien; Tan, Kar Ban; Hepp, Marco; Butz, Benjamin; Schönherr, Holger; Talib, Zainal Abidin; Md Salim, Nora Salina; Mohd Ghazali, Mohd Sabri; Lee, Oon Jew (Taylor and Francis, 2022)
High oil sorption, dynamic oil/water selectivity and oil retention are essential for advanced materials to remediate offshore oil spills. In this context, superoleophilic-hydrophobic kapok bundles, synthesized via a simple, one-step and energy efficient carbonization (300°C), were investigated as effective oil sorbents. It was shown that the surface roughness and intrinsic graphite phase of the kapok bundles were tunable by varying the carbonization temperature, thereby enhancing their oil sorption and retention. Lumen preservation enables the carbonaceous kapok bundles to exhibit tunable oil sorption capacities of 34.0 g/g – 95.5 g/g for various types of oil, unrivaled among other oil spill recovery methods. The origin of oil permeability into lumen is attributed to nanopores observed for the first time on the carbonaceous kapok fibers. The kapok bundles selectively absorbed oil slick under vigorous water vortex and demonstrated distinctly high oil retention of 100% under gravitation force. Multiple oil sorption-desorption and compression cycles (up to 15 times) demonstrate a considerable promise of the carbonaceous kapok bundles for high reusability with low environmental impact.